MEDIASI SEBAGAI SALAH SATU CARA DALAM PENYELESAIAN SENGKETA PERDATA DI LUAR PENGADILAN - ,, Yunimar (Fakultas Hukum Universitas Tamansiswa Padang, 2022)
As social beings, humans cannot let go of themselves depending on other humans to meet their needs. In this interaction, disputes often arise. The dispute is sometimes resolved immediately, and sometimes it is not. There are two ways to resolve the dispute, namely in court or out of court. One form of dispute resolution outside the court is mediation. There are many benefits in resolving disputes through mediation, and the most important thing is the result is a win-win solution, which is able to meet the psychological, legal and procedural needs of the parties.